Anticipation dialogs in Vermont’s system of mental healthcare: Sustaining the growth of a dialogic practice culture - Alpern, Zelda; Binshadler, Sarah; Oakley, Ashley (Frontiers in Psychology, 2023)
Open dialog is both a therapeutic approach and a way of organizing the system of mental healthcare that has been evolving in Finland since the 1980s. In Vermont, over the last decade, there has been an organic statewide effort to begin to integrate dialogic principles into the public system of mental healthcare. Because of the organic nature of these initiatives, there have not been coordinated systemic changes to support dialogic practices. To learn what visions participants in dialogically informed practice contexts have for the future as well as what structural innovations would support these visions anticipation dialogs were offered at three dialogically informed community mental health centers and one public psychiatric. The anticipation dialog was developed in Finland during the late 1980s to aid stuck professional and social networks in finding ways to move forward looking back from an imagined positive future. Twenty-seven multidisciplinary staff members and one service recipient participated in the dialogs. The authors conducted a multi-step process of thematic discourse analysis of all 4 anticipation dialogs. Findings underscore dilemmas entailed in growing a dialogic practice system, including the toll systemic uncertainty takes on workers in the system and the simultaneous pull to offer some amount of open-endedness to the system change process in the spirit of inclusiveness, mutual trust, democracy, and reducing hierarchy. Other key findings influencing sustainability of dialogic practices in community mental health include integrating dialogic work into roles rather than adding them to existing responsibilities. Our experiences indicate that anticipation dialogs may be a way of conducting systemic research that contributes to the forward momentum of system innovation. Offering a greater length of time for organizational anticipation dialogs would be valuable, as would centering the voices of clients and their networks.